Novel 4-Acrylamido-Quinoline Derivatives as Potent PI3K/mTOR Dual Inhibitors: The Design, Synthesis, and in vitro and in vivo Biological Evaluation - Ma, Xiaodong; Shen, Li; Zhang, Jiankang; Liu, Guoqiang; Zhan, Shuyu; Ding, Baoyue; Lv, Xiaoqing (Frontiers in Chemistry, 2019)
A novel structural series of quinoline derivatives were designed, synthesized and biologically evaluated as PI3K/mTOR dual inhibitors upon incorporation of C-4 acrylamide fragment. Consequently, all of them exerted remarkable inhibition against PI3Kα with IC50 values ranging from 0.50 to 2.03 nM. Besides, they exhibited submicromolar to low micromolar anti-proliferative activity against both prostate cancer PC3 and colorectal cancer HCT116 cell lines. In subsequent profiling, 8i, a representative compound throughout this series, also significantly inhibited other class I PI3Ks and mTOR. In PC3 cells, it remarkably down-regulated the crucial biomarkers of PI3K/Akt/mTOR signaling, including phos-Akt (Ser473), phos-Akt (Thr308), phos-S6 ribosomal protein (Ser235/236), and phos-4E-BP1 (Thr37/46), at the concentration as low as 5 nM. Moreover, in both human liver and rat liver microsomes, 8i displayed favorable metabolic stability with long elimination half-life. Further in vivo pharmacokinetic (PK) study demonstrated 8i possessed acceptable oral exposure, peak plasma concentration, and elimination half-life. Taken together, 8i, as a potent PI3K/mTOR dual inhibitor, merited further investigation and structural optimization.